Intraductal papillary neoplasm of the bile duct presenting with hepatogastric fistula: a case report and literature review - Chan, Wen-Hui; Chen, Chien-Ming; Wang, Shang-Yu; Wu, Ren-Chin; Chen, Tse-Ching; Lee, Hao-Kang; Lin, Cheng-Hui; Yeh, Chun-Nan (Frontiers in Oncology, 2023)
Intraductal papillary neoplasm of the bile duct (IPNB) is an uncommon entity characterized by papillary growth within the bile duct lumen. IPNB is regarded as a biliary counterpart of intraductal papillary mucinous neoplasm of the pancreas, which sometimes complicates with fistula formation to adjacent organs, mainly due to high-pressure related erosion from mucin-filled ducts. However, fistula formation from IPNB is quite rare. Here we report a case of IPNB complicated with hepatogastric fistula. Abdominal computed tomography (CT) and magnetic resonance imaging (MRI) revealed disproportional dilatation of left intrahepatic duct with intraluminal soft tissue nodules and fistulous connections to gastric high body. Endoscopy revealed ulcers with two fistulous orifices at upper gastric body. The patient underwent left hepatectomy with gastric wedge resection. Histopathology examination revealed IPNB with invasive cholangiocarcinoma, directly invading to gastric wall leading to hepatogastric fistula. In summary, we have presented the clinical, imaging and pathological findings, along with a comprehensive review of relevant literature, in order to enhance the understanding of this rare condition.